The Influence of Corporate Messages on the Product Portfolio - Biehal, Gabriel J.; Sheinin, Daniel A. (Journal of Marketing, 2007)
The authors examine factors that change the influence of corporate messages for forming judgments about products in the company's portfolio (i.e., transfer). Corporate messages transferred more than a product message onto other products in the company's portfolio. However, a product message had more influence than corporate messages for that product. Moreover, a corporate ability (quality) message transferred more to the portfolio than did a corporate social responsibility message. Finally, a competitive product message that preceded a company product message and was positioned similarly to a company product lessened corporate message diagnosticity, reducing transfer. However, this occurred only for a product in the same category but not for a product in a different one. The authors discuss the implications of these findings for corporate brand and product brand managers and suggest directions for further research.